2023
DOI: 10.1007/s11818-023-00398-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of drug-induced sleep endoscopy in Germany—an analysis based on claims data

Abstract: Background Drug-induced sleep endoscopy (DISE) has recently gained relevance as a diagnostic tool for obstructive sleep apnea (OSA). However, it is unclear to what extent and in which patient cohorts DISE is used in Germany. With introduction of specific coding for this method in 2021 (Operationen- und Prozedurenschluessel, OPS code), usage can now be analyzed based on diagnosis-related groups (DRG) claims data. Methods Aggregated data from all inpatient D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…44 This disparity in ease of prescription was especially notable in studies reporting a lower number of referrals to otolaryngology specialty clinics from primary care physicians, which may reflect a more complex referral process prior to diagnostic sleep, 34 whereas larger hospitals were more inclined to perform DISE for presurgical evaluation of OSA. 27 Patient education from providers was also a noteworthy factor in patient decision-making. 30 A 2011 study noted that general otolaryngologists often report a lack of requisite training and education for certain hypopharyngeal procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 This disparity in ease of prescription was especially notable in studies reporting a lower number of referrals to otolaryngology specialty clinics from primary care physicians, which may reflect a more complex referral process prior to diagnostic sleep, 34 whereas larger hospitals were more inclined to perform DISE for presurgical evaluation of OSA. 27 Patient education from providers was also a noteworthy factor in patient decision-making. 30 A 2011 study noted that general otolaryngologists often report a lack of requisite training and education for certain hypopharyngeal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…24 Sex disparities were also evident, with a 2016 study highlighting a greater surgical inclination among women, 25 whereas studies from Germany reported that women had a higher likelihood of receiving MAD as the preferred choice of treatment 26 and were also more likely to undergo DISE for presurgery evaluation. 27 Some studies also reported racial and ethnic disparities but had varied associations based on the type of study. Two large national database studies from the United States reported a lower likelihood of surgery among Black and Hispanic individuals, 25,28 whereas another single institutional study from the United States observed a higher number of Hispanic patients undergoing surgical treatment for OSA.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation